DOI: 10.17771/pucrio.acad.54808
|View full text |Cite
|
Sign up to set email alerts
|

Social Venture Leadership: Understanding Attributes and Processes for Innovation in Social Organizations

Abstract: To professors Dennis Barber III and Michael Harris for welcoming me at the East Carolina University and sharing enthusiasm for social entrepreneurship.To the members of the Examining Board, whose observations contributed significantly to the evolution of this work.To all professors and employees of IAG/PUC-Rio for their support and dedication. Particularly to Luiza Martins, Ruth Mello, and Beatriu Canto, from the Entrepreneurship Center (CEMP), for the academic partnership and sharing the same passion about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 219 publications
(489 reference statements)
0
1
0
Order By: Relevance
“…Leadership requires having the power to influences others. Several studies have established that the professional skills and competence that made venture leaders effective in the beginning stage of the business can inhibit them as the business expands needing more leading and managing [7,8]. Scholars have also identified that several leaders are successful in starting and creating a business alone.…”
Section: Venture Leadership and Influencementioning
confidence: 99%
“…Leadership requires having the power to influences others. Several studies have established that the professional skills and competence that made venture leaders effective in the beginning stage of the business can inhibit them as the business expands needing more leading and managing [7,8]. Scholars have also identified that several leaders are successful in starting and creating a business alone.…”
Section: Venture Leadership and Influencementioning
confidence: 99%